Computers and the law: mechanised searching of legal documents, 1975-1977 (UK Data Service, 1980)
This is a computer program designed to store and search the text of legal documents and to develop a small-scale working system which can be used by law students for practical searching in selected areas of statute and case law. The area of case law chosen for study was that relating to unfair dismissal. In the research programme, particular emphasis was placed on the development of a searching language to be used by lawyers and others in the interrogation of legal documents.